JOBMIX BETON MENGUNAKAN PASIR LUMAJANG DAN PENAMBAHAN ADDITIVE MASTERPOZZOLITH®402R - Ahmad Ridwan; Sigit Winarko; Eko Siswanto (Litbang Pemas - Universitas Islam Lamongan, 2018)
Concrete is an important element in a construction. The strength of the concrete is determined by the quality of the concrete. So that the mixture used must meet the standards, by using selected materials and adding other substances, it will produce a higher quality than SNI. Masterpozzolith® 402R additive is a mixture of concrete material that serves as a bonding enhancer on concrete, this material will react with cement and water so that when the element is fused it will produce a better bond between coarse and fine aggregates. In this study concrete will use lumajang sand and add the masterpozzolith® 402R additive as an additional material to achieve the desired high quality. with a concrete job mix using the K-200, it is expected to produce concrete with a quality above the specified target. The results of this study can include more than the targets that have been determined, with planning to use mutubeton K-200 the concrete produced can reach K-222, so the method is quite good when applied in construction.